2005
DOI: 10.1002/jso.20206
|View full text |Cite
|
Sign up to set email alerts
|

Favorable outcome of Ewing sarcoma family tumors to multiagent intensive preoperative chemotherapy: A single institution experience

Abstract: The intensive chemotherapy schedule, comprising of 5-6 cycles preoperatively, seems to maximize the percentage of tumor necrosis, thus improving outcome. Our study implies that this combined therapy may improve the prognosis of ESFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…However, severe acute toxicities were more frequent in the BuMel group, and the incidence of secondary malignancies in long-term survivors was not reported. Studies on other agents are more limited, thus no firm conclusion could be drawn at this stage 40 43 . To date, there is no standard treatment for refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe acute toxicities were more frequent in the BuMel group, and the incidence of secondary malignancies in long-term survivors was not reported. Studies on other agents are more limited, thus no firm conclusion could be drawn at this stage 40 43 . To date, there is no standard treatment for refractory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moschovi et al [ 18 ] reported that the overall survival rate of patients with ES/PNET has progressively improved as a result of an effective systemic treatment and adequate resection and radiation for local control. Furthermore, the research suggested that multiagent intensive chemotherapy before surgery can further improve the prediction of these tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic agent tried in combination are vincristine, cyclophosphamide, actinomycin D and doxorubicin. [6] Prognosis is poor and depends on age of patient at the time of diagnosis, tumor bulk, location and prescence secondaries. In our case patient underwent distal pancreatectomy and splenectomy and received adjuvant chemo-radiotherapy, and after 26 months she died of multiple liver, bone and lung metastasis [7].…”
Section: Discussionmentioning
confidence: 99%